Autonomic nervous system functions in obese children - Yakinci, C; Mungen, B; Karabiber, H; Tayfun, M; Evereklioglu, C (Elsevier Science Bv, 2000)
Childhood obesity is a complex syndrome, probably due to the multiplicity of contributing factors, contradictory literature information about etiology, prognosis, prevention and treatment. In the recent reports, autonomic nervous system (ANS) dysfunction has been documented in adult obesity. Autonomic nervous system functions in obese children are not clear. This study was planned to investigate autonomic nervous system function in childhood (7-13 years of age) obesity. Study and control groups consisted of 33 simple obese (23 boys and ten girls, mean age 9.5 +/- 1.4 years) and 30 healthy children (18 boys and 12 girls, mean age 10.1 +/- 1.8 years), respectively. Four non-invasive autonomic nervous system function tests (Orthostatic test, Valsalva ratio, 30/15 ratio, Heart rate responses to deep breathing) and general ophthalmic examination were performed on both groups. The difference between the obese and control groups was found statistically significant in Valsalva ratio, 30/15 ratio and Heart rate responses to deep breathing (P < 0.025), and insignificant in Orthostatic test (P > 0.05). Ophthalmic examinations were normal. The result of these tests suggested normal activity of sympathetic, and hypoactivity of parasympathetic nervous system, implying parasympathetic nervous system dysfunction as a risk factor or associated finding in childhood obesity. (C) 2000 Elsevier Science B.V. All rights reserved.
Keywords: autonomic nervous system; obesity; childhood